An electron in the field of two classical plane waves propagating in slightly different directions; Soviet Physics Journal; Vol. 18, iss. 1 - Bagrov V. G. Vladislav Gavriilovich; Gitman D. M. Dmitry Maksimovich; Zadorozhnyi V. N. Valery Nikolaevich; Shvartsman Sh. M. (1975, 1975)
Title screen